PERANCANGAN MEDIA PEMBELAJARAN TEKNOLOGI JARINGAN KABEL DAN NIRKABEL BERBASIS ANIMASI MENGGUNAKAN KINEMASTER - Jama Hendra, Risil; Elin Yuspita, Yulifda; Darmawati, Gusnita; Annas, Firdaus (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
This research is motivated by problems at SMK Pembangunan Bukittinggi, where there is a lack of learning media during the learning process. This causes students to tend to play rather than listen to the teacher when explaining the material. During the learning process, teachers only use limited printed books, so students lose interest due to the lack of variety in the learning methods presented. Therefore, interesting and creative educational resources are needed to increase students' learning motivation. This research adopts the Research and Development (R&D) model, which is used to produce and test a product. This research model follows the 4D approach (Define, Design, Develop, Disseminate). The validity of the product was tested by three experts in the field, the practicality was tested by Computer and Network Engineering teachers at SMK Pembangunan Bukittinggi, and the effectiveness was tested by students at the school. The test results showed a validity value of 0.83, a practicality of 0.93, and an effectiveness of 0.79. Thus, it can be concluded that the design of animation-based wired and wireless network technology learning media at SMK Pembangunan Bukittinggi is said to be very effective.